STUDI PERBANDINGAN KOSAKATA DASAR BAHASA MAKASSAR DIALEK BANTAENG DAN DIALEK TURATEA (SUATU TINJAUAN LEKSIKOSTATISTIK) - Tasniah, Siti; Suyatno, Suyatno; Supratno, Haris (International Conference on Humanity Education and Society (ICHES), 2024)
This study aims to describe the kinship relationship and the length of time of separation between the Bantaeng dialect and the Turatea dialect. The method used in this study both in data collection, analysis, and objective presentation of data is quantitative. This study focuses on objects without influencing or regulating natural phenomena regarding the basic vocabulary of the Bantaeng and Turatea dialects of the Makassar language. The results showed that (1) Two hundred of Moris Swadesh's vocabulary, 4 of which were excluded because they did not meet the requirements for further study, so that the words compared were 196 words left. From this data, it was found that there were 142 words or 72.44% of words that have identical pairs between Bantaeng dialect and Turatea dialect in phonemic correspondence, 5 words or 2.55%, phonetically similar 9 words or around 4.59%. (2) Makassar language with Bantaeng and Turatea dialects is a single dialect based on a standard error of 0.7 from the actual situation. From a comparison of Moris Swadesh's basic vocabulary, it is known that the Bantaeng dialect and the Turatea dialect are the only dialect at 171 years.